2005
DOI: 10.1146/annurev.med.56.082103.104540
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Clinical Importance of Haplotypes

Abstract: Advances in genotyping and sequencing technologies, coupled with the development of sophisticated statistical methods, have afforded investigators novel opportunities to define the role of sequence variation in the development of common human diseases. At the forefront of these investigations is the use of dense maps of single-nucleotide polymorphisms (SNPs) and the haplotypes derived from these polymorphisms. Here we review basic concepts of high-density genetic maps of SNPs and haplotypes and how they are ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
176
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(187 citation statements)
references
References 115 publications
6
176
3
2
Order By: Relevance
“…Matrix metalloproteinase 9 polymorphism and HIV therapy C Demacq et al polymorphisms, 36,37 it may be less informative when a causal connection between genetic variations and a phenotype is truly driven by a single polymorphism. 38 This may well be the case of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase 9 polymorphism and HIV therapy C Demacq et al polymorphisms, 36,37 it may be less informative when a causal connection between genetic variations and a phenotype is truly driven by a single polymorphism. 38 This may well be the case of this study.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis presents that complex traits have underlying genetic variants that occur with a relatively high frequency. 40,45 The importance of examining extended haplotypes of gene clusters has been clearly demonstrated in several studies. 46,47 In an analysis of IL-20/IL-24 extended haplotypes, the susceptibility effect to psoriasis with limited eruption (extent equal or below 10%) of the IL-24 haplotype GGGT did not withstand.…”
Section: Discussionmentioning
confidence: 99%
“…5 CK2 activity is elevated in many kinds of tumors. 6,7 Very specific inhibitors of CK2 have been developed. In previous experiments, we showed that one of these inhibitors, 4,5,6,7-tetrabromobenzimidazole (TBB), inhibited the growth of malignant pre-B lymphoblastic leukemia cells that express Bcr/ Abl P190.…”
Section: Figurementioning
confidence: 99%
“…6 The two SNPs resulted in strong linkage disequilibrium, and, although the small group of patients tested, SLC19A1 haplotype (C232C_T-233T) seems to be associated with a longer OS also suggesting that an altered folate metabolism could decelerate disease progression and a fatal outcome. In fact, rapidly dividing cancer cells have an increased folate requirement for maintaining DNA synthesis.…”
mentioning
confidence: 91%